“Standstill” - Quina, Francis Paolo M. (Philippine Humanities Review; Vol 23: 2021-2022, 2025)
Ian and Lisa are running late to their own engagement party, which is being thrown by Lisa’s mother, even though she does not approve of Ian. Using a navigation app to help them navigate across Metro Manila to get to the venue, they take unfamiliar alleys and streets, which also turn out to be traffic-congested. During the long ride, the couple fight and this leads them to re-evaluate their relationship.